How do you characterize the interactions between a teacher and their students about fractions and proportions in the context of energy performance calculations? - Benrherbal, Abderrahmane; Rioux , Miranda (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2024)
This research focuses on the didactic interactions between a teacher and their students about fractions and proportions in the context of calculating energy performance in a science and technology classroom at the Secondary IV level. The analysis of interactions is done according to the didactic incidents that most often emerge from the students’ errors. The analysis also identifies the assistance provided to pupils according to the types of proximity as well as certain effects of the didactic contract. Our results indicate that the mobilization and use of fractions and proportions in the context of calculating the energy efficiency of a machine is not self-evident for students and influences didactic interactions when teaching and learning this concept.